HUBUNGAN PELAKSANAAN PEMBERIAN OBAT DENGAN PRINSIP DUA BELAS BENAR TERHADAP TINGKAT KEPUASAN PASIEN DI RUANG RAWAT INAP RSD MANGUSADA BADUNG - Sudarminingsih, Ni Kadek Pande Eka; Susila, I Made Dwie Pradnya; Kusuma, A.A. Ngurah Nara; Sumawati, Ni Made Risna (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Nurses are the spearhead of services that greatly affect patient satisfaction as service users in the hospital. One of the nursing services that provided by nurses is administering drugs. The twelve correct principles of drug administration are the most current principles of medication, consisting of correct patient, correct drug, correct dose, correct method of administration, correct time, correct documentation, correct health education regarding medication, patient right to refuse, correct assessment, correct evaluation, correct reaction to food and correct reaction to other drugs. This study aimed to determine the correlation between the implementation of drug administration with twelve correct principles on the level of patients’ satisfaction in the Inpatient Ward of Mangusada Badung General Hospital.This research was a quantitative study with observational methods and cross sectional design, the sample in this study were patients and the population of nurses in Mangusada Badung General Hospital according to the inclusion and exclusion criteria selected by purposive sampling of 58 patients and 58 nurses. The research was conducted for 1 month. Data were analyzed using nonparametric rho spearman test at a significance level of ? 0.05, p value was 0.000 <0.05. It showed that there was a significant correlation between the implementation of drug administration with Twelve correct principles on the level of patients’ satisfaction in the Inpatient Ward of Mangusada Badung General Hospital. It is expected that health workers, especially nurses, can apply the principles of correctness in administering drugs to increase patient satisfaction.